The Relationship between Characters and Conflict in the Short Story Jannatul Athfal by Naguib Mahfouz: A Structuralist Review - Wahyuni, Indraati; Nabilah, Iffatin (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
This study aims to understand the relationships between characters and the conflicts that occur in the short story entitled Jannatul Athfal written by Naguib Mahfoudz. This short story tells the confusion of a child in understanding religious differences with his friends, which is expressed through a warm and intense conversation with his father. This study uses a descriptive qualitative approach by analyzing the intrinsic elements in the story through the structuralism method. The results of this study indicate that the relationships between the characters in the short story are formed through the conversation between the child and his father, which occurs dynamically. In addition, this relationship also shows emotional feelings, the process of learning moral values, and an understanding of social life. The conflict that arises occurs due to differences in understanding and social disputes that increasingly develop into deeper issues regarding the meaning of life. In terms of structure, the conflict acts as a driving force of the story as well as a means of conveying the values ​​of tolerance and humanity. Thus, the structure of the relationships between the characters and the conflict in this short story shows that this work is not only intended for children, but also for adult readers because it contains a critical reflection on how society accepts differences in social life.